Fiscal Policy to Mitigate Climate Change : A Guide for Policymakers - Mooij, Ruud A. (International Monetary Fund, 2012)
Efforts to control atmospheric accumulations of greenhouse gases that threaten to heat up the planet are in their infancy. Although the IMF is not an environmental organization, environmental issues matter for its mission when they have major implications for macroeconomic performance and fiscal policy. Climate change clearly passes both these tests.